Mechanisms for Scaffold-Mediated Regulation of Kinase Activity in the Wnt Signaling Pathway - Fagnan, Erin (My University, 2019)
Cellular signaling is a complex process involving numerous pathways. Many of these pathways are connected through shared proteins, creating branch points that may result in crosstalk between pathways. It is not fully understood how protein activity can be regulated by a variety of different upstream signals and still maintain specificity. Scaffold proteins may act as a solution to this specificity issue by physically assembling signaling proteins within a specific pathway, such as a MAPK cascade. There are many models for how scaffold proteins regulate protein activity, all of which are based on the idea that scaffold proteins increase specificity by increasing reaction rates for the proteins they bring together. Even though this idea has laid the foundation for many studies in the signaling field, we still lack a thorough kinetic analysis of scaffold function and its effect on specificity. In order to determine if scaffold proteins actually increase reaction rates as a mechanism for specificity, we measured GSK3β reaction rates with several substrates in a minimal, biochemically reconstituted system of the Wnt signaling network. We found that the Wnt scaffold Axin produces a modest, 2-fold enhancement of the rate of phosphorylation of the Wnt substrate β-catenin. Surprisingly, we found that Axin significantly slows the rate of phosphorylation of a non-Wnt substrate. Together, these data suggest that Axin alone is not sufficient to accelerate a specific kinase-substrate reaction. Instead, Axin can promote signaling specificity by suppressing kinase reactions with competing, non-Wnt pathway targets. Further, these newly identified properties of Axin reinforce an emerging trend that scaffold proteins can regulate kinase activity through a diverse set of mechanisms.
Thesis (Ph.D.)--University of Washington, 2019
Keywords: Axin; Cell Signaling; GSK3; Scaffold Proteins; Wnt pathway; Chemistry; Biochemistry; Chemistry